A New Tumor-Immunotherapy Regimen based on Impulsive Control Strategy. (March 2020) - Aghaeeyan, Azadeh; Yazdanpanah, Mohammad Javad; Hadjati, Jamshid
Abstract: Autologous tumor infiltrating lymphocyte (TIL) therapy refers to a kind of immunotherapy in which the tumor-resident lymphocytes are harvested, cultured, and then transferred into the patient. In spite of some well-known TILs expansion recommendations, there is a lack of well-established TILs injection protocol. This paper addresses the challenge using a feedback-based control strategy. Utilizing Lyapunov technique, a novel dose calculation method is proposed which considers TILs pharmacokinetics. Then, to determine the timing of TILs administration, the concept of therapeutic window in pharmacy is exploited. The resultant therapy protocol is both practical and implementable while it ensures tumor remission. Comparing with previous studies, the proposed method takes the discontinuity of TILs delivery process into consideration. Computational results suggest the following therapy protocol which is in accordance with experimental observations: A few high dose TILs injections are required. Then, there is a longtime drug free interval.